First report of charge-transfer induced heat-set hydrogel. Structural insights and remarkable properties. Issue 21 (17th May 2016) - Bhattacharjee, Subham; Maiti, Bappa; Bhattacharya, Santanu
Abstract : Structural insights into the self-assembly of a donor and an acceptor and their co-assembly into heat-set hydrogel with remarkable properties. Abstract : The remarkable ability of a charge-transfer (CT) complex prepared from a pyrene-based donor (Py-D) and a naphthalenediimide-based acceptor (NDI-A) led to the formation of a deep-violet in color, transparent hydrogel at room temperature (RT-gel). Simultaneously, the RT-gel was diluted beyond its critical gelator concentration (CGC) to obtain a transparent sol. Very interestingly, the resultant sol, on heating above 70 °C, transformed into a heat-set gel instantaneously with a hitherto unknown CGC value. Detailed studies revealed the smaller globular aggregates of the RT-gels fuse to form giant globules upon heating, which, in turn, resulted in heat-set gelation through further aggregation. The thermoresponsive property of Py-D alone and 1 : 1 Py-D : NDI-A CT complex was investigated in detail which revealed the hydrophobic collapse of the oxyethylene chains of the CT complex upon heating was mainly responsible for heat-set gelation. Thixotropy, injectability, as well as stimuli responsiveness of the RT-gels were also addressed. In contrast, heat-set gel did not show thixotropic behavior. The X-ray diffraction (XRD) patterns of the xerogel depicted lamellar packing of the CT stacks in the gel phase. Single crystal XRD studies further evidenced the 1 : 1 mixed CT stack formation in the lamellae and also ruled out orthogonal hydrogen bonding possibilities among the hydrazide unit in the CT gel although such interaction was observed in a single crystal of NDI-A alone. In addition, a Ag + -ion triggered metallogelation of NDI-A and nematic liquid-crystalline property of Py-D were also observed.